Effects of Sperm Parameters on Pregnancy Rate in Patients Undergoing Intrauterine Insemination - Mehmet Solakhan; Mustafa Demir (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: In this study, the effects of sperm parameters on the success of intrauterine insemination were investigated.